Removal of phosphate from synthetic wastewater by using marsh clam (polymesoda expansa) shell as an adsorbent - Noorul Hudai, Abdullah; Xian, Ong Jing; Yi, Chiew Zhi; Yuan, Ng Shi; Mohamad Syahrul Syazwan, Yaacob; Nur Atikah, Abdul Salim; Noraziah, Ahmad; Zainab, Mat Lazim; Maria, Nuid; Faizuan, Abdullah (AMG Transcend Association, 2023)
Phosphate pollution is becoming a serious problem worldwide. It leads to increased algae growth, resulting in eutrophication, which affects the water bodies’ quality, the lives of aquatic organisms, and the daily routines of humankind. Previous research has proven effective chemical precipitation for phosphate removal, but the cost is high and may generate waste material. Thus, this study proposed the marsh clam (Polymesoda expansa) shell as an absorbent due to its abundant availability, low cost, and high absorption capacity of phosphorus. This study was conducted to investigate the removal efficiency of phosphate using raw marsh clamshells. In this study, the concentration of aqueous solution using KH2PO4 was fixed to 10 mg/L of PO4 3− as the initial concentration. The 2 g of mass absorbent (0.075mm, 0.15mm, 0.30 mm, 0.60 mm, 1.18 mm, 2.36 mm) mixed with 100mL of KH2PO4 solution in the conical flask in a certain time interval. The orbital shaker was used for mixing the KH2PO4 solution with the adsorbent. Moreover, HACH DR 6000 Spectrophotometer is then used to determine phosphate concentration for initial and final results. The results were verified using kinetic and isotherm models, where kinetic models used Pseudo First Order (PFO) and Pseudo Second Order (PSO). The isotherm model used the Freundlich and Langmuir models. The optimum performance of the batch experiment showed by the PSO model had the highest correlation coefficient (R2 = 0.9965) and the lowest Fe value of 0.086. This study showed that marsh clamshells could remove PO4 3− effectively for 1.18–2.36 mm size with the highest removal efficiency of 73%. The removal of phosphate from domestic wastewater can be an alternative wastewater treatment in tertiary treatment in the field of the wastewater treatment plant.